PENGGUNAAN MEDIA PERMAINAN ULAR TANGGA BAGI PENINGKATAN KETERAMPILAN SISWA MENULISKAN KATA (Penelitian Pre-Eksperiment pada Pembelajaran Bahasa Inggris di Kelas III SD Negeri 1 Sukaharja Kecamatan Rajadesa Kabupaten Ciamis ) - KURNIAWATY, Nia (2014)
This research is motivated by the possibility of implementing Snakes and Ladders game in elementary school students as English writing ability enhancement. Snakes and Ladders game (in Bahasa, it is called Ular Tangga) is commonly used as a media for enhancing writing ability. Snakes and Ladders game has an advantage in enhancing writing ability. On the other hand, English writing ability enhancement in elementary school, especially for third grade students is not yet optimized. Thus, Snakes and Ladders game could be a solution. Empirical evidence was generated through Pre-eksperiment research that was held in state elementary school Sukaharja 1 (SD Negeri 1 Sukaharja). Problem formulation of this research is how the implementation of Snakes and Ladders game enhances English writing ability of state elementary school Sukaharja 1 third grade students. The motivation of this research is to find out the picture about the improvement of English writing ability in state elementary school Sukaharja 1 third grade students. This research uses quantitative method, meanwhile data collection technique in this research comprises test assessment. The data of this research is 24 third grade students of state elementary school Sukaharja 1, Subdistrict: Rajadesa, District: Ciamis. The hypothesis assessment shows 0.56 n-gain. And than, the result of Wilcoxon test with assymp sig is 0,000. Because asymp sig 0,000 < 0,05,Ha is rejected and H0 is accepted. The results indicates that Snakes and Ladders game implementation improves students' English writing ability in elementary school. Keywords: Media, Snakes and Ladders game, writing ability